(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
At the end of 2019, the Indonesian National Standards Agency issued new regulations regarding procedures for earthquake resistance planning in building and non-building structures or SNI 1726:2019. The existence of new regulations will certainly be one of the issues that need attention regarding the safety of buildings designed based on old regulations or SNI 1726:2012. This paper aims to compare spectral acceleration designs based on SNI 1726:2012 and SNI 1726:2019 for several cities in Indonesia, namely Medan, Banda Aceh, Bengkulu, Padang, Bandar Lampung, Yogyakarta, Surabaya, Palu, Ambon and Jayapura. The comparison results show that in hard (SC) and medium (SD) soil conditions, almost all cities surveyed experienced increased spectral acceleration values except for Medan and Surabaya, where the values were the same. The increase in the spectral acceleration value in hard (SC) and medium (SD) soil conditions was very significant in the cities of Palu, Jayapura, and Bengkulu. However, in soft soil (SE), almost all survey cities experienced a decrease in spectral acceleration, except for Medan and Surabaya, where the spectral acceleration values were the same. Considering that the results of spectral design comparisons in several cities have increased, it is important to re-evaluate the existing building structures.